Impacts And Strategies for Handling Covid-19 In Indigenous People: A Scoping Review (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
The COVID-19 pandemic is a major health emergency that causes significant suffering and many deaths among indigenous people worldwide. During the pandemic, indigenous communities have higher rates of health problems than the general population. This review explores the impact and strategies for handling COVID-19. This scoping review aims to draw key concepts from the available literature that underpins a research area. The literature search was conducted on eight databases, namely PubMed, DOAJ, Science Direct, Cochrane, Wiley, ProQuest, and Garuda, in July-November 2022. The online search engine was Google, and the keywords for the search were